Building a React app from scratch (O'Reilly, 2017)
"This course shows you how to build a React application, as a notepad project, from start to finish. We go through a setup of the tools you need; explain the basics of React (i.e., covering topics such as components, JSX, state, props, lifecycles, and state management); and get your project started by demonstrating how to code the required components. You'll learn how CSS and backends fit into a React app, and then work with modular CSS and firebase to finalize your app. Course requirements include a working knowledge of HTML, CSS, JavaScript, and ES6 syntax."--Resource description page